1998
DOI: 10.1038/sj.onc.1201512
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of PTEN/MMAC1, a candidate tumor suppressor gene, and its homologue, PTH2, in small cell lung cancer cell lines

Abstract: Loss of heterozygosity (LOH) at chromosome 10q23-q25 is frequent in small cell lung cancer (SCLC), indicating the presence of putative tumor suppressor genes. PTEN/ MMAC1, a newly cloned candidate tumor suppressor gene at 10q23, was mutated in multiple human cancers. We investigated whether mutations of PTEN/MMAC1 play an important role in SCLC tumorigenesis. We examined 16 SCLC cell lines for PTEN/MMAC1 mRNA expression by reverse-transcriptase polymerase chain reaction (RT ± PCR) and potential mutations by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…an expressed PTEN pseudogene on chromosome 9 has been identified (Kim et al 1998: Teng et al 1998). Crosshybridization to RNA derived from this pseudogene may therefore account for some of the PTEN transcript profile.…”
Section: )mentioning
confidence: 99%
“…an expressed PTEN pseudogene on chromosome 9 has been identified (Kim et al 1998: Teng et al 1998). Crosshybridization to RNA derived from this pseudogene may therefore account for some of the PTEN transcript profile.…”
Section: )mentioning
confidence: 99%
“…4B), 12 developed PNEC hyperplasia, and 16 had no obvious morphological defects. Because Pten mutations are also found in a significant number of human SCLCs (19,20), we speculated that mutations in Pten could cooperate with p53/Rb mutations to promote SCLC development. Indeed, loss of Pten, in addition to p53 and Rb, significantly accelerated tumor initiation and progression.…”
Section: Pulmonary Neuroendocrine Cells Have Very Limited Potential Tomentioning
confidence: 99%
“…Our study's most interesting finding was related to the expression of the PI3K class III gene: the expression ratio was 2.5 and 11 times greater than in normal tissue in ECa and Dys, respectively. It has been reported that activation of the PI3K signal pathway is closely related to the malignancy of human malignant tumors 10,13,16,17,30) , and it is known that this signal Watanabe S et al Fig. 1 Immunohistochemical studies of H&E stain and p-AKT antibody expression in each region of human tongue (original magnification ‫,04ן‬ ‫)002ן‬ A, Normal Tissue (NT).…”
Section: Gene Analysis Using Cdna Microarraymentioning
confidence: 99%